Keragaman Gen NRAMP-1 dan INOS pada Ayam Sentul Seleksi - Ardiyana, M.; Sumantri, C.; Murtini, S.; Sartika, T. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
NRAMP-1 protein and INOS enzyme have been shown as deffense mechanism against bacteria and virus infection. These genes have not been investigated in Sentul Selection chickens. This study was aimed to determine the polymorphism of NRAMP-1 and INOS in Sentul Selected chickens. A number of 172 sentul selected chickens was observed for NRAMP-1 and INOS genes using PCR-RFLP. The frequency of genotypes and alleles, polymorphic information content and Hardy-Weinberg equilibrium status (HWE) were analyzed. Polymorphism in NRAMP1|SacI and INOS|AluI were observed. The population was in HWE for both genes. NRAMP1 gene frequencies had higher TC genotypes and INOS gene frequencies had higher CC genotypes (P<0.05) in Selected Sentul chickens. Furthermore, the NRAMP1 and INOS genes, the frequency of allele C was higher than the T allele. It could be concluded that NRAMP-1 and INOS gene has potential to propose has associated with immune traits in Sentul chicken.